2023
DOI: 10.3390/ijerph20032644
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Community-Based Suicide Prevention in the Context of Rural Australia: A Qualitative Study

Abstract: Suicide rates in rural communities are higher than in urban areas, and communities play a crucial role in suicide prevention. This study explores community-based suicide prevention using a qualitative research design. Semi-structured interviews and focus groups asked participants to explore community-based suicide prevention in the context of rural Australia. Participants recruited ((n = 37; ages 29–72, Mean = 46, SD = 9.56); female 62.2%; lived experience 48.6%) were self-identified experts, working in rural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…According to the WHO health system, the health system change framework includes 1) service delivery; 2) human resources; 3) the treatment process and technology used; 4) health information systems; 5) financing, and 6) leadership (WHO, 2010). Caring leaders with a strong vision can motivate communities to deliver health services, including mental health services (Grattidge et al, 2023;Moon et al, 2023;Warren et al, 2023). Spiritual leaders such as Imam, Kyai, Priests, and Buddhist monks make arrangements, give messages about health when they feel health problems in times of safety or emergency, and try to provide solutions for their communities (Luetke Lanfer et al, 2022;Valente & Pumpuang, 2006).…”
Section: The Role Of Social Communities In the Provision Of Accessibl...mentioning
confidence: 99%
See 1 more Smart Citation
“…According to the WHO health system, the health system change framework includes 1) service delivery; 2) human resources; 3) the treatment process and technology used; 4) health information systems; 5) financing, and 6) leadership (WHO, 2010). Caring leaders with a strong vision can motivate communities to deliver health services, including mental health services (Grattidge et al, 2023;Moon et al, 2023;Warren et al, 2023). Spiritual leaders such as Imam, Kyai, Priests, and Buddhist monks make arrangements, give messages about health when they feel health problems in times of safety or emergency, and try to provide solutions for their communities (Luetke Lanfer et al, 2022;Valente & Pumpuang, 2006).…”
Section: The Role Of Social Communities In the Provision Of Accessibl...mentioning
confidence: 99%
“…namely the fully assisted category, directed category, and independent category. This difference in the category of diagnostic labels can reduce the stigma against children with special needs (Grattidge et al, 2023). After 40 days of observation aimed at categorizing ability levels and eliminating stigma, it is evident that children with special needs continue to develop following their circumstances.…”
Section: Psychological Intervention By Combining Community and Spirit...mentioning
confidence: 99%
“…Several studies have reported higher suicide rates in rural areas than in urban areas. Furthermore, population outflow (depopulation) is considered a characteristic of areas with high suicide rates ( Fushimi et al, 2005 , Grattidge et al, 2023 ). The trend observed in this study is in accordance with these findings.…”
Section: Relationship Between Population Inflow and Outflow And Suici...mentioning
confidence: 99%
“…Existing international work underscores barriers, such as stigma or aspects of rural culture [19,20], or reinforces addressing barriers, such as healthcare shortages [21]. Efforts must be community-led and engage the entire community, not just clinical professionals, leveraging partnerships [22]. Such work must identify and address self-identified community needs [22], but also use trauma-informed strategies [19].…”
Section: Of 16mentioning
confidence: 99%
“…Efforts must be community-led and engage the entire community, not just clinical professionals, leveraging partnerships [22]. Such work must identify and address self-identified community needs [22], but also use trauma-informed strategies [19].…”
Section: Of 16mentioning
confidence: 99%